Evaluation of Gordes Zeolite Deposit of Turkey forIndustrial Uses - Mahmut Kilic, Ahmet; Kilic, Ozen (Asian Journal of Chemistry, 2010)
In this study, the G”rdes natural zeolite deposits were characterized and assessed potentially in industrial uses. In the present work, chemical, mineralogical, physical properties (brightness, hardness, abrasive, bulk and dry density, specific gravity, apparent porosity, grain density, water and oil absorption, bleaching capacity of the original material, bleaching capacity of the activated material, specific surface area, pore diameter, void ratio, angle of repose), cation exchange capacity and thermal stability of zeolites were investigated. The sample presented fairly high specific surface area, porosity, adsorption and cation exchange capacity. Overall, it has been understood that the Gordes zeolite could be used for agricultural production, chemical binder, cat litter, animal feed and fertilizer, absorbents for gas purification, building materials, fillers, pool filter media and waste treatment.